Understanding child development : for adults who work with young children - Charlesworth, Rosalind. 4 0 16; 5 (Australia : Thomson / Delmar Learning, 2008)
Presents information on each stage of child development from birth through age eight, discussing physical, motor, cognitive, and emotional growth.
A brief look at the young child -- Developmental and learning theories -- Studying the young child -- How learning takes place -- Learning through play -- The adult role in learning : general characteristics -- The adult role in learning : family and sociocultural factors -- Conception and prenatal development -- Heredity, environment, and development -- Birth and the first two weeks -- Infancy : theory, environment, and culture -- Infancy : health and physical and motor skills development -- Infancy : affective development -- Infancy : cognitive development -- The toddler : autonomy and physical and motor development -- The toddler : affective development -- The toddler : cognitive development --Physical development, health, safety and nutrition : ages three to six -- The cognitive system and concept development -- Oral language development and use -- Written language : development and everyday use -- Intelligence and creativity -- The adult role and cognitive development -- The nature of affective development : theory, emotion, and personality -- Social development -- The adult role in affective development -- Preschool to primary : bridging the gap -- The primary child : physical and motor development -- The primary child : affective development -- The primary child : cognitive development and schooling -- A look at the whole child -- Action for children.
Includes bibliographical references and index.
Adult
Keywords: 2 -- 0; 6; Child development. -- 20; 20; 2